REVERSE TRANSFORMATION IN THE PLAY “HAYAVADANA” BY GIRISH KARNAD (Journal of Pharmaceutical Negative Results, 2022)
Well Eminent and versatile writer Girish Karnad’s third popular play in English is Hayavadana. This paper deals with the reverse transformation of the humans in the journey of completeness. Human failed to retain their identity in search of completeness while the animal succeeded in regaining its identity. The central theme- The story of Devadatta and Kapila’ is based on the tale from the Kathasaritsagara. But the main theme is borrowed from Thomas Man’s –The Transposed Heads. The horse regained its full form with its neigh in the end of the story and thus achieved its completeness. On the other hand, the child retained its human smile and become a complete human-being. The Hayavadana was happy to become a full animal while the humans Kapila and Devadatta lost their lives without attaining their completeness. Padmini also unsatisfied with the end result and performed sati. Darwin’s theory says that humans are evolved from Animals. But in Hayavadana, the human attains the animal form in reverse transformation. The mother of Hayavadana loved the horse and got married to it. When he became a human being, she rejected to accept him. So she was cursed to become a horse. She was happy to lose her identity as a human and ready to become a horse. Her love for a horse made her a horse and thus she achieved her completeness. Hayavadhana wanted to attain its completeness whether it will be a horse or may be a human. At-last he became a complete horse but with a human voice. The son of Padmini exchanged his neigh with Hayavadana’s human voice. Thus the mother and her son Hayavadana achieved completeness in reverse transformation by becoming a horse.